Faktor-Faktor yang Mempengaruhi Pendapatan Ayam Pedaging Mitra - Nina Maksimiliana Ginting; merry dawapa; Riza Fachrizal; Nurliah Nurliah; Abdul Rizal (Universitas Musamus, Merauke, Papua, 2021)
This study aims to analyze the factors that affect the income of partner broilers in the study area. This research was conducted in Merauke District. The location selection was carried out purposively. The time of the research was conducted from May to November 2020. Sampling in this study used the census method. Respondents in this study were 13 partner broiler breeders. The analysis technique used in this research is multiple linear regression. The results show that the coefficient of determination (R2) obtained is 0.995, indicating that broiler income (Y) can be explained by the independent variable X. Partially or the t test shows that the cost of seeds, feed costs and labor affects income, while partially the cost of medicine - medicine does not affect income.